Clinical characteristics and mortality risk factors of premature infants with carbapenem-resistant Klebsiella pneumoniae bloodstream infection - Zengyuan Yu; Lifeng Li; Ping Cheng; Hongbo Zhang; Shujing Xu (Scientific Reports)
Abstract Due to the resistance of carbapenem-resistant Klebsiella pneumoniae (CRKP) to most antibiotics, CRKP treatment is challenging, which results a high mortality rate. CRKP infection poses a significant challenge for infection management and treatment, especially among neonates and premature infants. Therefore, it is important to understand the clinical characteristics of CRKP bloodstream infection (BSI) in premature infants and identify the related risk factors for death. This study aims to explore and analyze the clinical characteristics and risk factors affecting mortality of BSI caused by CRKP in premature infants. A retrospective study was conducted in a Children’s Hospital in Henan to analyze clinical data of premature infants with CRKP BSI admitted from January 2015 to December 2022. Univariate and multivariate logistic regression models were utilized to investigate risk factors affecting mortality. Receiver operating characteristic curves were employed to evaluate the predictive value of different indicators on mortality, and differences in area under the curve (AUC) were compared using Stata 17 SE. A total of 96 premature infants with CRKP BSI were enrolled, including 70 patients in the survival group and 26 in the death group. At the onset of infection, 69 (71.9%) patients exhibited persistent tachycardia (heart rate > 180 beats/min), 61 (63.5%) had fever, and 59 (61.4%) experienced apnea episodes. Concurrent meningitis (OR 9.588, 95% CI 1.401–57.613, P = 0.021), concurrent necrotizing enterocolitis (NEC) (OR 7.881, 95% CI 1.672–73.842, P = 0.032), and the maximum vasoactive-inotropic score (VIS) value within 48 h of onset (OR 1.467, 95% CI 1.021–1.782, P = 0.001) were identified as independent risk factors for mortality. The univariate analysis showed that ceftazidime-avibactam (CAZ/AVI) treatment and appropriate early antimicrobial treatment were significantly associated with survival (P < 0.05). The combined predictive AUC for mortality in premature infants with CRKP BSI using the maximum VIS value ≥ 52.5 points within 48 h of onset, concurrent NEC, and purulent meningitis was 0.931 (95% CI 0.856–1.000) with a sensitivity of 92% and specificity of 85.7%. CRKP BSI was a significant mortality risk in premature infants. It is crucial to administer proper antimicrobial therapy in order to increase survival rates of the patients. CAZ/AVI has the potential to improve outcomes in this particular population; however, further research is required to evaluate the effectiveness of specific treatment in premature infants.